Subtitusi Tepung Daun Kelor dalam Pembuatan Cup Cake - Esteria Priyanti; Favian Arif Setiawan Midi (Garina, 2020)
Subtitution of kelor leaves flour in making Cup Cake hopefully become new innovation in Cup Cake product and can improve economical amount of kelor plant. Purpose of this research are: 1) Knowing the sensory characterictic of Kelor Leaves Cup Cake; 2) Knowing people acceptance to Kelor Leaves Cup Cake. Method used in this research by using library method, documentation, experiment, and hedonic test. Experiment in making Kelor Leaves Cup Cake held in laboratory of culinary art study program at AKS Ibu Kartini, Jl. Sultan Agung No. 77, Gajahmungkur District, Semarang City. Addition percentage of kelor leaves flour in making Kelor Leaves Cup Cake as amount of 5%, 10%, and 15% from flour weight. Result of this research shows that Kelor Leaves Cup Cake product has sensory characteristic included sweet flavour with taste of kelor leaves, colour from greeny yellow until dark green, tekxture hard sponged and specific aroma of Cup Cake (margarine aroma with kelor leaves aroma). Panelists aceptance to Kelor Leaves Cup Cake by hedonic test result shows that panelists choose Kelor Leaves Cup Cake with addition of kelor leaves flour as amount of 15 %. It is concluded that there is innovation opportunity from Cup Cake with addition of kelor leaves flour.